Nanopartikel Kitosan dan Ekstrak Daun Bugenvil: Karakterisasi dan Aplikasinya untuk Mengendalikan Bean common mosaic virus strain Blackeye Cowpea: Nanoparticles of Chitosan and Bougainvillea Leaf Extract: Characterization and Its Application to Control Bean common mosaic virus strain Blackeye Cowpea - Islami, Nisa Fadhila; Damayanti, Tri Asmira; Santoso, Sugeng; Akhiruddin, Akhiruddin (Jurnal Fitopatologi Indonesia, 2024)
Nanoparticles of Chitosan and Bougainvillea Leaf Extract: Characterization and Its Application to Control Bean common mosaic virus strain Blackeye CowpeaChitosan and bougainvillea crude leaf extract is known able to control viruses including Bean common mosaic virus strain Blackeye Cowpea (BCMV-BlC). To reduce the raw material usage and to increase their effectiveness and stability, it is necessary to formulate them using nanoparticle (NP) technology. The research aimed to synthesize nanoparticles of chitosan (Kit-NP), bougainvillea leaf extract (EDB-NP), and their combination (KEDB-NP) using modified ionic gelation method, characterized and evaluated the potential of NPs in controling BCMV-BlC on indicator plant Chenopodium amaranticolor. Kit-NP, EDB-NP, and KEDB-NP were successfully synthesized, with characteristic average particle sizes of 99.72, 163.68, and 221.42 nm, respectively under TEM and have a spherical form under SEM. The FTIR analysis showed that KEDB-NP functional groups were hydroxyl, alkene, amine, aromatic ring, and organohalogen aliphatic compounds. Chenopodium amaranticolor leaves sprayed by those of NPs, as well as their non-NP treatment at a concentration of 100–800 ppm before virus inoculation showed an average number of necrotic local lesion (NLL) significantly lower than untreated control and was not significantly different among concentrations. Those treatments before virus inoculation significantly prolong the incubation period and reduced NLL formation with effectiveness ranging 67.5%–100% in compared with application after virus inoculation. The NPs concentrations between 100 and 300 ppm which is applied before virus inoculation showed the best effectiveness in inhibiting NLL formation. Those of NPs synthesized using greatly less amount of their bulk materials, but their effectiveness are comparable to their non-NP forms in controlling BCMV.